102 Ethnic differences in endothelial function in chronic heart failure. (9th June 2011) - Shantsila, E; Gill, P S; Lip, G Y H
Abstract : Background: Endothelial dysfunction is characteristic of patients with heart failure (HF) and is associated with an increased risk of future cardiovascular events. However, data on ethnic differences in endothelial function in HF are scarce. In this study we aimed to compare parameters of macro- and micro-vascular endothelial function and arterial elasticity in HF age- and sex-matched patients of different ethnic origin: (i) white European, (ii) south Asian and (iii) African-Caribbean. Additionally, SA patients with systolic HF were compared to two matched control groups: (i) south Asian patients with coronary artery disease without HF(disease controls)and (ii) south Asian "healthy controls". Methods: We recruited 186 age/sex-matched patients with HF (ejection fraction <40%) of SA (n=43, age 66.5±11.1 years), white (n=44, age 68.4±9.4 years) and African-Caribbean (n=21, age 69.2±10.3 years) origin; as well as 36 disease controls (age 64.0±10.6 years) and 40 healthy controls (n=40, age 63.3±9.24 years). Macrovascular endothelial function was assessed as brachial artery flow mediated dilation in response to hyperaemia (FMD) and glyceryltrinitrate were assessed by vascular ultrasonography (iE33, Philips, USA). Microvascular endothelial function was evaluated by laser Doppler flowmetry of forearm skin (DRT4, Moor Instruments, UK) after iontophoresis of acetylcholine and sodium nitroprusside. Arterial stiffness was quantified by pulse wave velocity and augmentation index using (Sphygmocor, Australia). Results: Compared to disease controls and healthy controls south Asian patients with HF had impaired microvascular response to acetylcholine (390±302%, 549±264%, and 123±95.5%, respectively, p<0.05) and reduced FMD (7.12±3.64%, 11.8±4.66%, and 4.86±4.88%, respectively). HF patients of south Asian origin had impaired microvascular endothelial function (response to acetylcholine123±95.5%) compared to white (258±15.6%) and African-Caribbean (286±17.3%) groups (p>0.05). HF patients of white origin had higher FMD than south Asian (4.86±4.88%) and African-Caribbean (5.36±3.24%) patients (p<0.05). No difference in glyceryltrinitrate- and sodium nitroprusside-mediated (endothelial-independent) response was observed between study groups. In south Asian subjects, parameters of pulse wave velocity and augmentation index did not differ between those with HF and those in control groups. No ethnic differences were detected in pulse wave velocity. Conclusion: South Asian patients with HF have impaired micro- and macro-vascular endothelial function, but preserved arterial elastic properties. Significant ethnic differences in endothelial function are present in patients with HF.